ESTIMASI NILAI DOSIS PADA PEMERIKSAAN CT SCAN KEPALA DEWASA BERDASARKAN NILAI CTDIvol DAN DLP - Ni Nyoman Sri Wikanadi; I Putu Eka Juliantara; Made Purwa Darmita (Perhimpunan Radiografer Indonesia (PARI), 2022)
ABSTRACT Background: Estimating the exact dose in CT Scan patients can be done by referring to an optimization index called DRL (Diagnostic Reference Level). Currently, the DRL for CT-Scans is expressed in CTDIvol (Computed Tomography Dose Index Volume) and DLP (Dose Length Product). The purpose of this study was to analyze the distribution of radiation dose values ​​on a CT scan of the adult head based on the CTDIvol and DLP values ​​referring to the IDRL reference from BAPETEN. Methods: This research is descriptive quantitative research with an observational approach. The Samples in this study were all patients who underwent Non-Contrast Head CT-Scan examinations at the radiology installation of Prof.Dr.I.G.N.G. Ngoerah Hospital, Denpasar for the period January-June 2022. Analysis of Results The estimation of radiation dose values ​​on CT Scan examinations of the adult head was based on the recapitulation of the distribution of CTDIvol and DLP values ​​obtained then compared with the IDRL 2021 values. Results: CTDIvol values ​​on non-Contrast head CT examination for all patients have varied values ​​with the lowest value of 23.28 mGy, the highest value of 62.7 mGy, an average of 47.58 mGy, and the 3rd quartile value of CTDIvol is 49.84 mGy. With the 75th percentile CTDIvol value of 49.84 mGy while the DLP value on the Head CT Examination varied in each patient with the lowest DLP value of 700.12 mGy*cm and the highest DLP value of 1597.19 mGy*cm and an average value of 1597.19 mGy*cm. DLP is 1057.95 mGy*Cm and the 3rd quartile value of DLP is 1133 mGy*cm. Conclusion: The CTDIvol and DLP values ​​for Non-Contrast Adult Head CT Scan examination at Prof.Dr.I.G.N.G. Ngoerah Hospital Denpasar are still below the reference from BAPETEN in IDRL 2021.